VOICES FROM THE FIELD: SOCIAL STIGMA AND HEALTHCARE PREJUDICES TOWARDS THE TRANSGENDER COMMUNITY OF LAHORE - Saba Azeem; Tayyaba Sohail; Zafar Iqbal; Sadaf Abid; Nousheen Naz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The access to quality healthcare services is a fundamental right of every human being but transgender community in Pakistan is regularly denied of it. The aim of this paper was to understand the underlined constructs of social stigmatization about transgender community and associated barriers in access to healthcare services. The study was conducted using qualitative research design. The data have been drawn from 20 in-depth interviews using purposive sampling. Only those transgenders were recruited who had an ailment requiring atleast 3 to 4 visits to a doctor for complete recovery. Furthermore, triangulation of method was used by conducting 10 semi-structured interviews with the healthcare providers at four public sector hospitals at Lahore to know about their competencies and specialization in treating transgender people. The study used thematic analysis, where themes were inferred from the collected data. Findings of the stud revealed that transgender were least interested in a medical checkup. They had the anticipated fear of being discriminated at public healthcare facility. This situation warranted self-medication of transgender. Furthermore, transgender experienced both delayed routine preventive care and delayed medical emergency care when sick or injured. It was also revealed that doctors discriminated against transgender, considering them the cause for discomfort to other patients. The healthcare providers appeared to be lacking medical and social competencies to deal with the specialized healthcare needs of transgender. The study proposed policy intervention to eliminate social stigma and to create an enabling environment for transgender at healthcare outlets.